OmpR-Mediated Transcriptional Regulation and Function of Two Heme Receptor Proteins of Yersinia enterocolitica Bio-Serotype 2/O:9 - Jaworska, Karolina; Nieckarz, Marta; Ludwiczak, Marta; Raczkowska, Adrianna; Brzostek, Katarzyna (Frontiers in Cellular and Infection Microbiology, 2018)
We show that Yersinia enterocolitica strain Ye9 (bio-serotype 2/O:9) utilizes heme-containing molecules as an iron source. The Ye9 genome contains two multigenic clusters, hemPRSTUV-1 and hemPRST-2, encoding putative heme receptors HemR1 and HemR2, that share 62% amino acid identity. Expression of these proteins in an Escherichia coli mutant defective in heme biosynthesis allowed this strain to use hemin and hemoglobin as a source of porphyrin. The hemPRSTUV-1 and hemPRST-2 clusters are organized as operons, expressed from the phem−1 and weaker phem−2 promoters, respectively. Expression of both operons is negatively regulated by iron and the iron-responsive transcriptional repressor Fur. In addition, OmpR, the response regulator of two component system (TCSs) EnvZ/OmpR, represses transcription of both operons through interaction with binding sequences overlapping the −35 region of their promoters. Western blot analysis of the level of HemR1 in ompR, fur, and ompRfur mutants, showed an additive effect of these mutations, indicating that OmpR may regulate HemR expression independently of Fur. However, the effect of OmpR on the activity of the phem−1 promoter and on HemR1 production was observed in both iron-depleted and iron-replete conditions, i.e., when Fur represses the iron-regulated promoter. In addition, a hairpin RNA thermometer, composed of four uracil residues (FourU) that pair with the ribosome-binding site in the 5′-untranslated region (5′-UTR) of hemR1 was predicted by in silico analysis. However, thermoregulated expression of HemR1 could not be demonstrated. Taken together, these data suggest that Fur and OmpR control iron/heme acquisition via a complex mechanism based on negative regulation of hemR1 and hemR2 at the transcriptional level. This interplay could fine-tune the level of heme receptor proteins to allow Y. enterocolitica to fulfill its iron/heme requirements without over-accumulation, which might be important for pathogenic growth within human hosts.